The Role of Teachers’ Non-Verbal Communication in ELT Classroom - Negi, Janak Singh (Journal of NELTA, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The role of non-verbal behavour in English classroom plays an important role for teaching content and skills. Based on this assumption, this article attempts to shed light on this hitherto unexplored area of research in the Nepalese context based on the observation by the author at various higher secondary schools in Nepal. The findings show that teachers' non-verbal behaviors play a highly important and essential role on learners' motivation in language classroom. Key words: non-verbal communication, paralanguage, information processing DOI: 10.3126/nelta.v14i1.3096 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 101-110